THE EFFECT OF DISPERSING AND STABILIZING ADDITIVE ON THE STABILITY OF UPGRADED COAL WATER MIXTURE - DATIN F. UMAR; BUKIN DAULAY; HIROMOTO USUI; YOSHIYUKI KOMODA (Puslitbang tekMIRA, 2007)
The upgraded brown coal water mixture (UBCWM) stability with several dispersing and stabilizing additives was studied based on coal sedimentation time history. UBCWM was filled up in a settling column; which has four holes in the upper, upper middle, bottom middle and middle side to take samples. Results indicate that the addition of Naphthalene sulfonate formaldehyde condensate (NSF) as dispersant together with S-194 some kinds of bio polysacharide with long branches produced by Dainippon Pharmaceutical Co. Ltd. as stabilizer, produces UBCWM with the best stability compare with that by using polystyrene sulfonate (PSS) and polymethacrylate (PMA) together with carboxyl methyl cellulose (CMC) and S-60 also some kinds of bio polysacharide, but without branches pro- duced by Dainippon Pharmaceutical Co. Ltd . Even the addition of S-194 results UBCWM with good stability, from the economical point of view, the addition of S-194 is a problem. The price of S-194 is expensive, whereas CMC is abundant and cheap. Therefore, the use of CMC as stabilizing additive was also effective in preparing stable UBCWM according to the stability of the UBCWM by using S- 194 and CMC is not significantly different.